Primary hypogonadism in the Borjeson-Forssman-Lehmann syndrome. - Weber, F T (1978)
A 28-year-old man with mental retardation and multiple congenital malformations was found to have the classical features of Borjeson-Forssman-Lehmann syndrome. Endocrine evaluations showed primary hypogonadism as the underlying endocrine abnormality rather than hypopituitarism as suggested in earlier reports.